Melhoria do condicionamento acústico de salas de aula existentes a partir medições e simulações - Gutterres, Christian Vargas (2023)
The work involves the acoustic evaluation of a classroom at the Technology Center of the Federal University of Santa Maria and a proposal for an internal modification that results in better acoustic conditioning. First, the room is acoustically measured according to the relevant standards, its reverberation time and its initial decay time being calculated for six microphone positions. Then the room is acoustically modeled and simulated. A procedure for adjusting the surfaces absorption coefficients is carried out in order to approximate the simulated results to the measured ones, since there is great uncertainty in these coefficients. Next, an acoustic conditioning project for the room is presented in order to seek to reduce the reverberation times to values closer to the ideal, as well as to increase the definition in the room. Finally, the room with the recommended acoustic treatment is simulated again. The measurement results are presented, the comparative results of the measurement versus simulation and the two simulations are compared (before and after the proposed acoustic treatment), showing the substantial improvement in reverberation times and the definition parameter, strongly correlated to speech intelligibility . Naturally, after carrying out the recommended acoustic treatment, a second acoustic measurement will be necessary in order to confirm the improvements foreseen in the simulation for its acoustic parameters.